Frequency and Prognosis of Pulmonary Metastases in Newly Diagnosed Gastric Cancer - Sun, Zepang; Liu, Hao; Yu, Jiang; Huang, Weicai; Han, Zhen; Lin, Tian; Chen, Hao; Zhao, Mingli; Hu, Yanfeng; Jiang, Yuming; Li, Guoxin (Frontiers in Oncology, 2019)
Purpose The purpose of this study was to analyze the frequency and prognosis of pulmonary metastases in newly diagnosed gastric cancer using population-based data from SEER. Methods Patients with gastric cancer and pulmonary metastases (GCPM) at the time of diagnosis in advanced gastric cancer were identified using the Surveillance, Epidemiology, and End Result (SEER) database of the National Cancer Institute from 2010 to 2014. Multivariable logistic and Cox regression were performed to identify predictors of the presence of GCPM at diagnosis and factors associated with all-cause mortality and gastric cancer-specific mortality. Survival curves were obtained according to the Kaplan-Meier method and compared using the log-rank test. Results We identified 1104 patients with gastric cancer and pulmonary metastases at the time of diagnosis, representing 6.02% of the entire cohort and 15.19% of the subset with metastatic disease to any distant site. Among entire cohort, multivariable logistic regression identified six factors (younger, upper of stomach, intestinal-type, later T staging, later N staging and presence of more extrapulmonary metastases to liver, bone and brain) as positive predictors of the presence of pulmonary metastases at diagnosis. Median survival among the entire cohort with GCPM was 3.0 months (interquartile range: 1.0-9.0mo). Multivariable Cox model in SEER cohort confirmed five factors (diagnosis at previous period, black race, adverse pathology grade, absence of chemotherapy and presence of more extrapulmonary metastases to liver, bone and brain) as negative predictors for overall survival. Conclusions The findings of this study provided population-based estimates of the frequency and prognosis for GCPM at time of diagnosis. These findings may provide preventive guidelines for screening and treatment of PM in GC patients. Patients with high risk factors should be given more attention before and after diagnosis.